2020
DOI: 10.3399/bjgp20x711017
|View full text |Cite
|
Sign up to set email alerts
|

Bringing together child health professionals and dental experts to tackle oral health in children

Abstract: BackgroundIn the UK, poor oral health among children continues to be a major public health concern. Primary care professionals are encouraged to take a proactive approach in engaging parents and carers to develop better oral health practices for their children. Unfortunately, research has shown that patients are often exposed to inconsistent and at worst conflicting advice.AimTo increase the confidence of primary care professionals in their knowledge surrounding preventative oral health and ensure the delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…By improving their oral health literacy and incorporating oral health into the routines of well-childcare, they can help prevent oral disease, improving not only children's oral health but their general health as well [65]. Studies have shown that a couple of hours of training is enough to help primary care physicians accurately diagnose caries and identify high-risk children who need dental referrals [41,[66][67][68]. Preventive measures initiated during the first years of life can significantly reduce the risk of developing dental caries and the need for more expensive restorative procedures later in life [43].…”
Section: Discussionmentioning
confidence: 99%
“…By improving their oral health literacy and incorporating oral health into the routines of well-childcare, they can help prevent oral disease, improving not only children's oral health but their general health as well [65]. Studies have shown that a couple of hours of training is enough to help primary care physicians accurately diagnose caries and identify high-risk children who need dental referrals [41,[66][67][68]. Preventive measures initiated during the first years of life can significantly reduce the risk of developing dental caries and the need for more expensive restorative procedures later in life [43].…”
Section: Discussionmentioning
confidence: 99%
“…MECC is recommended regardless of the patient's purpose of contact or the practitioner's speciality 32 . In recent years, the effectiveness of MECC in human healthcare has been explored across a number of domains, including chronic conditions in adults and children, radiography, dentistry, vaccine uptake and smoking cessation during the COVID pandemic 34–39 …”
Section: Introductionmentioning
confidence: 99%
“…32 In recent years, the effectiveness of MECC in human healthcare has been explored across a number of domains, including chronic conditions in adults and children, radiography, dentistry, vaccine uptake and smoking cessation during the COVID pandemic. [34][35][36][37][38][39] A key question concerns whether veterinarians believe they have a role to play or the skills needed for MECC. While there is a developing body of literature as to whether and how veterinarians engage clients in the weight management of their pets, 24,[40][41][42][43][44][45][46][47][48] this paper also draws on the evidence in human healthcare contexts, which specifically identifies practitioner perspectives on MECC, barriers to MECC and studies identifying when and how MECC has efficacy.…”
Section: Introductionmentioning
confidence: 99%